SENAM REMATIK PADA LANSIA DI PANTI JOMPO BASILAM DI KOTA PADANGSIDIMPUAN TAHUN 2020 - Siregar, Hotma Royani; Nasution, Nurul Hidayah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Osteoarthritis is a degenerative joint disease related to cartilage damage which causes pain and interfere to perform activities of daily living. The aim of this community service is to help patients with osteoarthritis to reduce their intensity of pain through rheumatic gymnastics. The applied method was rheumatic gymnastics. The results of this project showed that the average intensity of pain during pre-test was 4 and in post, it became by 3. It implies that the average reduction was 1. Therefore, it can be said that this project managed to reduce the pain intensity.